Apoyo en la empresa AP Constructores S.A.S en procesos constructivos, en el área de interventoría como pasante en ingeniería civil (2022)
This document shows us in detail the analysis, realization and development of a Work Log, Traffic and Transportation Management Plan (P.M.T) and a comprehensive work management plan that will support the company AP Constructores S.A.S located in the city o f Sogamoso (Boyacá). The objective of this report is focused on a better construction management in civil works that allows improving the work on site; as well as implement strategies and alternatives for the development of these. For the development of th is project, all those needs and difficulties that the company has had during the execution and completion of the internship have been taken into account, among which it was found that during the execution of each of the works a log was necessary that would allow a better organizational scheme that would give order to the performance of each job, thus facilitating the application of construction processes.